Exploring Cultural Conflicts and Synthesis in Indian English Novels: A Comparative Analysis of Kamala Markandaya and Arun Joshi’s Novels (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This research paper examines the thematic concern of cultural conflict and synthesis in the Indian English novels of Kamala Markandaya and Arun Joshi, two eminent literary figures who reflect the complexities of postcolonial Indian identity. Through a comparative lens, the study focuses on how these authors portray the tension between traditional Indian values and Western influences, as well as the possibility of cultural reconciliation. Markandaya’s narratives emphasize the external socio-cultural dynamics, especially in rural and diasporic settings, while Joshi delves into the internal, psychological struggles of the modern Indian individual. By analyzing selected novels—Nectar in a Sieve and The Nowhere Man by Markandaya, and The Foreigner and The Strange Case of Billy Biswas by Joshi—this paper highlights how both writers navigate the spectrum of conflict and synthesis, offering distinct yet complementary visions of Indian cultural identity in transition.